Fano resonance based on long range surface phonon resonance in the mid-infrared region - Zhang, Xiangli (2020)
Surface plasmon polaritons with noble metals lack the capability to restrain an optical field in the long wavelength region, while surface phonon polaritons with polar di-electric crystals have been regarded as a potential low-loss alternative. In this paper, long range surface phonon resonance (LRSPhR) is designed to operate in the mid-infrared (MIR)wavelength regime with a narrow resonance dip. Furthermore, by coupling a photonic wave-guide with the LRSPhR, strong coupling between waveguide mode and long-range surface phonon polariton has been realized to form high Q Fano resonance. By employing such structure as the index sensor, it is shown that the bulk sensitivity and surface sensitivity can reach∼9000 and 266.9 RIU–1, respectively, which shows a great enhancement comparing with the one based on merely LRSPhR. The proposed configuration can be a promising platform for MIR biochemical sensing.